2017
DOI: 10.1007/s11356-017-8891-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrients on Chlorella pyrenoidosa for treatment of phenolic effluent of coal gasification plant

Abstract: The ability of Chlorella pyrenoidosa, a freshwater microalga, to degrade phenolic effluent of coal-based producer gas plant under ambient conditions was investigated. C. pyrenoidosa was able to grow in high-strength phenolic effluent. Major contaminant present in the effluent was phenol (CHOH). The effluent has 1475.3 ± 68 mg/L of initial total phenolic concentration. The effect of nutrients used for algal cultivation in phenol degradation was analyzed by inoculating four different concentrations, viz.,1, 2, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…7 Response surface plot (3D) of (a) final biomass expressed as dry weight (mg L −1 ) and (b) growth rate as a function of initial light intensity and initial total phenolic compounds exposed to the medium, thereby enhancing dye removal. Furthermore, Stephen and Ayalur (2017) found that Chlorella pyrenoidosa at an initial inoculum of around 3-4 g L −1 could remove phenol up to 95% when supplemented with nutrients. CCD RSM revealed that increasing initial phenolic compounds and light intensity significantly enhanced the phenol removal efficiency by photodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…7 Response surface plot (3D) of (a) final biomass expressed as dry weight (mg L −1 ) and (b) growth rate as a function of initial light intensity and initial total phenolic compounds exposed to the medium, thereby enhancing dye removal. Furthermore, Stephen and Ayalur (2017) found that Chlorella pyrenoidosa at an initial inoculum of around 3-4 g L −1 could remove phenol up to 95% when supplemented with nutrients. CCD RSM revealed that increasing initial phenolic compounds and light intensity significantly enhanced the phenol removal efficiency by photodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…2020). However, Chlorella pyrenoidosa has been reported for heterotrophic (Stephen and Ayalur 2017a) and mixotrophic (Stephen and Ayalur 2017b) degradation of phenol with a capacity reaching 91–95% of 295 mg phenol l −1 . Nevertheless, the phycoremediation of phenol by Scenedesmus sp.…”
Section: Factors Affecting Phenol Phycoremediationmentioning
confidence: 99%
“…Nevertheless, it should be taken into account the green house gas (GHG) emission reduction, the decline in sludge formation, low‐energy requirement, simple operation and maintenance and the disinfection effect of algal photosynthesis on most pathogenic bacteria (e.g. Escherichia coli ) and viruses, via the pH increment with the assimilation of CO 2 , H + ions and bicarbonate by algae, which collectively add to the advantage of wastewater treatment via microalgae (Stephen and Ayalur 2017b). CO2(gas)+H2O(aq)H2CO3(aq)H2CO3H+0em0em0.333333em+ HCO3HCO3H+0em0em0.333333em+ CO32…”
Section: Phycoremediation Of Phenol‐polluted Petro‐industrial Effluents and Techno‐economic Sustainable Futurementioning
confidence: 99%